Antiproliferative Efficacy of Zerumbone-Loaded Nanostructured Lipid Carrier in BALB/C Mice Model of Breast Cancer - Rahman, Heshu Sulaiman; Abdullah, Rasedee; Othman, Hemn Hassan; Jalal Ali, Othman; Abdul, Ahmad Bustamam; Abdul Samad, Nozlena; SM, Chartrand; Swee, Keong Yeap; Hossienpour, Mahnaz (Department of Veterinary Services Malaysia, 2014)
Recently, we showed that the antiproliferative effect of ZER-NLC on Jurkat cells is through the apoptotic intrinsic pathway via activation of caspase-3 and -9, release of cytochrome c (cyt-c) from mitochondria into cytosol, and subsequent cleavage of polyADP-ribose polymerase (PARP). However, there has been no available information of ZER-NLC affects murine breast cancer cells in vivo. Thus, In this study, in vivo effects of ZER-NLC on murine breast cancer 4T1 cells were investigated. Outcomes of histopathology, immunohistochemistry and TUNEL assays of BALB/c mice bearing breast cancer revealed that the number of cancer cells were significantly decreased in mammary gland tissues after four weeks of oral administration of various doses of ZER-NLC.